Evaluating Sustainable Educational Technology Adoption Models to Bridge Institutional Innovation and Community Driven Learning Practices - Tiwuk Widiastuti; Dewantoro Lase; Firman Pratama (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This study explores the integration of community driven learning practices in the adoption of educational technology and its impact on sustainability. With the rapid advancement of digital tools and platforms, higher education institutions have increasingly adopted online and hybrid learning models to enhance teaching and learning. However, despite the potential benefits, aligning institutional goals with community needs remains a significant challenge. This research utilizes a mixed methods approach, combining stakeholder surveys, policy analysis, and comparative case studies to evaluate the effectiveness of both top down and community aligned adoption models. The findings reveal that community driven models, which involve local stakeholders in the decision making process, lead to higher engagement, better adoption rates, and greater long term sustainability compared to top down approaches. Stakeholders, including educators, students, and administrators, reported that participatory decision making fostered a sense of ownership and ensured the relevance of adopted technologies. The study also identifies key sustainability factors, including participatory decision making, long term community engagement, and contextual relevance, which are crucial for ensuring that educational technologies remain effective and beneficial over time. However, challenges such as resistance to change, lack of resources, and unequal access to technology were found to hinder the successful implementation of sustainable models. The research concludes with practical recommendations for educational institutions and policymakers to adopt community aligned models and ensure equitable access to technology. Future research directions are suggested to further explore the balance between institutional innovation and community driven learning, with a focus on long term outcomes and the adaptability of these models across different educational contexts.